Synthesis, structural characterization, biological evaluation and molecular docking studies of new platinum(ii) complexes containing isocyanides. (24th April 2018) - Fereidoonnezhad, Masood; Shahsavari, Hamid R.; Abedanzadeh, Sedigheh; Nezafati, Ali; Khazali, Ali; Mastrorilli, Piero; Babaghasabha, Mojgan; Webb, James; Faghih, Zeinab; Faghih, Zahra; Bahemmat, Samira; Beyzavi, M. Hassan
Abstract : Platinum(ii ) complexes with various isocyanides are prepared and their biological activities are studied. Abstract : Herein, new Pt(ii ) complexes [R′2 Pt(CNR)2 ] (1a–c ; R′ = Me and2a–c ; R′ = p -tolyl) were synthesized by the reaction of the precursor complexes cis, cis -[Me2 Pt(μ-SMe2 )2 PtMe2 ], A, and cis -[( p -tolyl)2 Pt(SMe2 )2 ], B, with four and two equivalents of different types of isocyanide ligands (CNR; R =a ; t -butyl, b ; benzyl, andc ; cyclohexyl isocyanide), respectively. All complexes were characterized by FTIR and NMR spectroscopies, and the structure of2b was confirmed by single-crystal X-ray determination. The evaluation of the cytotoxicity of1a–c and2a–c against three human cancer cell lines, namely A549 (non-small cell lung cancer cell line), SKOV3 (human ovarian cancer cell line), and MCF-7 (human breast cancer cell line), revealed promising antitumor activities for1b and2a in comparison with that of the standard cisplatin. Moreover, 1b effectively rendered apoptosis-inducing activities to the MCF-7 cancer cell line. The electrophoresis mobility shift assays on plasmids as well as molecular docking studies on DNA structures effectively revealed the specific binding site, binding mode, and the best orientation of the complexes to DNA.